PENGARUH METODE ABC RUNNING TERHADAP HASIL BELAJAR TEKNIK LARI JARAK PENDEK 60 METER - Mizar Agari; Victor Gaberius Simanjuntak; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe problem in this study is whether there is an influence of the ABC running method on learning basic techniques in a short distance of 60 meters. This study aims to determine how much influence the ABC running method has on the basic motion of running in physical education learning. This research is an experimental study with the form of pre experimental design. The population in the study amounted to 98 people. The sample in this study used purposive sampling technique with a total of 20 people. Data analysis with T-Test. The normality test and homogeneity test were carried out before the t-test. Based on the results of data analysis, findings are found, as follows; The results showed that the t-test is t-count (11.18)> t-table (2.025) which means there is an influence of the ABC running method on a short run of 60 meters. Based on these results, it is expected that the abc running method can be used as an alternative to improve the learning outcomes of basic techniques in short-distance running on students.. Keyword: ABC running, Learning Outcomes, Method, Sprint